Three new microcerberids (Isopoda: Microcerberidae) from subterranean freshwater habitats in Texas, USA. Issue 35 (17th September 2021) - Hutchins, Benjamin T.; Schwartz, Benjamin F.; Coleman, William T.
ABSTRACT: The stygobiontic genus Texicerberus gen. nov. and the three species T. amistad sp. nov., T. schotteae sp. nov., and T. castilloi sp. nov. are described from freshwater aquifer or hyporheic sites across central and western Texas, USA. The status of the new genus and species is based on morphological characters that distinguish them from all other described Microcerberidae from both marine and freshwater environments. Cephalon without rostral projection, coxae II–IV rounded, medial margin of antenna article 3 angulate but not produced as spine, male pleopod II endopod uniramous, and male pleopod IV biramous are among the characters that distinguish Texicerberus gen. nov. from other genera in the family. Collected from deep karst aquifer wells, karst springs, and the hyporheic zone along the Rio Grande (Rio Bravo del Norte), these three new species represent the first documented occurrences of Microcerberidae in Texas and substantially increase the described diversity in the family in North America and from freshwater environments globally. Additional sampling, especially in the hyporheic zone, is expected to reveal additional diversity in Texas. Future collection and analysis of molecular data will be required to understand the evolutionary relationships among these and other species.